Legal Responsibility for Environmental Pollution and Damage from Natural Resource Exploration - Andy Tonggo Michael Sihombing; Rolib Sitorus; Joy Zaman Felix Saragih (PT FORMOSA CENDEKIA GLOBAL, 2024)
Exploitation of natural resources has positive and negative impacts on human life, in this case this study aims to determine the legal responsibility for environmental pollution and damage due to the exploration of natural resources in Indonesia. The research method used is normative legal research, with an approach through laws and regulations that focus on legal products that regulate environmental pollution. The sources of legal materials to be used consist of primary legal materials, including the 1945 Constitution of the Republic of Indonesia; Law of the Republic of Indonesia Number 32 of 2009 concerning Environmental Protection and Management; Law Number. 6 of 2023 concerning Job Creation; Regulation of the Minister of Environment Number. 4 of 2021 concerning Environmental Impacts, and the Criminal Code (KUHP). While secondary legal materials come from literature studies, such as books relevant to the law and research results from legal experts and legal journals. The results achieved are that legal responsibility for environmental pollution and damage in Indonesia includes a comprehensive approach involving aspects of civil law, criminal law, and state administrative law. The government, through various regulations and law enforcement mechanisms, seeks to protect the environment by imposing sanctions and requiring polluters to undertake remediation.